Quantitative Structure Activity Relationship (QSAR) Analysis of Antimicrobial Escherichia Coli by Transition Metal Complexes With 8-Hydroxyquinoline - Muliadi Muliadi (SAINTIFIK@: Jurnal Pendidikan MIPA, 2026)
Structural modeling and computational optimization of molecular geometry have been carried out using ChemDraw Ultra 12.0 and Gaussian-09. The measured parameters are electronic descriptors, hydrophobic descriptors and steric descriptors. The result of geometry optimization using the DFT method (B3LYP) with a set base of 6-31G is the total energy and heat of formation of each complex compound. Determination of the relationship between descriptors and antimicrobial activity which includes Log P, Polarizability, PSA, EHOMO, ELUMO, ∆EG, MD, Harary Index, Randic Index, and Wiener Index. The results of the correlation indicate a relationship with antimicrobial activity. Furthermore, the best HKSA equation model was determined by multilinear regression analysis using the SPSS 25 IMB package program.